Analysis and validation of femur bone data using finite element method under static load condition. (August 2019) - Mathukumar, S; Nagarajan, VA; Radhakrishnan, A
Humans face bone fracture when they unfortunately met an accident, which requires timely medical attention for healing and repairing the fractured bone; otherwise that paralyzes their life. 3D modeling technique with computational method is very helpful at the side of doctors for healing and repairing the damaged bones. Fractional bone healing is one of the natural processes, which regain the mechanical reliability of the bone to a limited level of failures. The relationship between the biology and mechanics has introduced a new branch namely biomechanics. Various biomechanics models were used to identify the fracture for different patients and helps in the fracture treatment. The aim of this work is to find out the high stress concentration area of the femur bone, which has been extracted as image from computer tomography scanner. The retrieved noise-free femur bone image is tested by the static load condition with the help of the finite element analysis. The result obtained from the testing of different loads has been compared with the existing literature. It is found that the femur bone has tensile and compressive stress, and the neck area of the femur is at a very high stress concentration. The outcome of this work is much supportive to orthopedic surgeons in femur surgery and bone prosthesis by avoiding experiments on femur bone.